2001
DOI: 10.1901/jeab.2001.76-75
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Primary Reinforcement on Pigeons' Initial‐link Responding Under a Concurrent‐chains Schedule With Nondifferential Terminal Links

Abstract: The effect of primary reinforcement on initial-link responding under concurrent-chains schedules with nondifferential terminal links was assessed in 12 pigeons. The iniitial and terminal links were variable-interval schedules (always the same for both alternatives). The positions (left or right key) of the initial-link stimuli (red or green) were randomized while the correlation between color and food amount remained constant within each condition. The terminal-link stimuli were always presented on the center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 32 publications
4
18
2
Order By: Relevance
“…Impaired learning about conditioned reinforcers may not, however, be detected in the acquisition of preference in concurrent chains schedules. For example, although conditioned reinforcers (i.e., terminal link stimuli) contribute to initial link preference [38], pigeons prefer an initial link leading to larger reinforcement even when the terminal links are not differentially signaled [39]. In the current study, the location of the lever associated with large reinforcement was consistent during baseline sessions.…”
Section: Discussionsupporting
confidence: 55%
“…Impaired learning about conditioned reinforcers may not, however, be detected in the acquisition of preference in concurrent chains schedules. For example, although conditioned reinforcers (i.e., terminal link stimuli) contribute to initial link preference [38], pigeons prefer an initial link leading to larger reinforcement even when the terminal links are not differentially signaled [39]. In the current study, the location of the lever associated with large reinforcement was consistent during baseline sessions.…”
Section: Discussionsupporting
confidence: 55%
“…At least procedurally, the delays of reinforcement that were studied here are analogous to the terminal-link durations of a concurrent chain, but only if the same stimulus occurs during both terminal links (see, e.g., Ploog, 2001;Williams & Fantino, 1978). Such schedules have been studied but never, to our knowledge, with repeated reversals of the schedule contingencies.…”
Section: Discussionmentioning
confidence: 99%
“…Using a concurrent chained VI VI chained VI VI schedule, Ploog (2001) found that pigeons generally preferred longer-duration reinforcers when differential initial-link stimuli were correlated with nondifferential terminal-link stimuli with respect to reinforcer duration. Ploog suggested that reinforcer duration and not conditioned reinforcers presented in the terminal links of the concurrent-chain schedules used in the experiment were controlling response allocation in the initial links.…”
Section: Stimuli Correlated With Reinforcer Durationmentioning
confidence: 99%